2016
DOI: 10.4154/gc.2016.18
|View full text |Cite
|
Sign up to set email alerts
|

Application of innovative technologies in landslide research in the area of the City of Zagreb (Croatia, Europe)

Abstract: This paper describes the application of advanced technologies for landslide detection, mapping and monitoring in the City of Zagreb since 2010. Airborne Light Detection and Ranging (LiDAR) data are used to visually identify landslides in the Podsljeme Zone over an area of 180 km 2 for the purpose of landslide inventory mapping. The total number of landslides in the analyzed area (approx. 1,600 landslides) is estimated based on the average landslide density (9 landslides per square km) from the most reliable ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…More recently, Bernat Gazibara et al, 2014a,b described landslide events triggered by intensive rainfall. Moreover, Mihalić Arbanas et al, 2016 identified the lack of a suitable landslide inventory as one of the critical issues in landslide risk management in the City of Zagreb. As a result, a LiDAR based landslide inventory map for the 21 km 2 in this study area was derived (Bernat Gazibara et al, 2019a,b), followed by a susceptibility assessment (Bernat Gazibara et al, 2023).…”
Section: Study Areamentioning
confidence: 99%
“…More recently, Bernat Gazibara et al, 2014a,b described landslide events triggered by intensive rainfall. Moreover, Mihalić Arbanas et al, 2016 identified the lack of a suitable landslide inventory as one of the critical issues in landslide risk management in the City of Zagreb. As a result, a LiDAR based landslide inventory map for the 21 km 2 in this study area was derived (Bernat Gazibara et al, 2019a,b), followed by a susceptibility assessment (Bernat Gazibara et al, 2023).…”
Section: Study Areamentioning
confidence: 99%
“…Based on previous landslide investigations, Jurak et al (2008) concluded that the geological contact between the Miocene or Quaternary clayey silty soils and the Miocene sandy silts is highly susceptible to sliding due to different permeability of sediments and periodical water saturation. The preparatory causal factors of slope instabilities in Podsljeme area depend on geomehanical properties of soils, geomorphological processes and different types of man-made processes (Mihalić Arbanas, Krkač, & Bernat, 2016). Preliminary analysis based on two predominating landslide casual factors, deposit types prone to sliding (upper Miocene and Quaternary sediments) and slopes inclination of 5°-55°, showed that 76% of the pilot area can be identified as landslide-prone area.…”
Section: Study Areamentioning
confidence: 99%
“…All reported landslides caused damage to houses and roads, which implies that the (re)activation of landslides in forests were not reported (Bernat et al, 2014b). Moreover, the local authorities do not have insight into the landslide location, so the main problem with the current practice of landslide risk management in the City of Zagreb is the lack of a suitable landslide inventory and geotechnical report archive (Mihalić Arbanas et al, 2016).…”
Section: Study Areamentioning
confidence: 99%
“…According to Mihalić Arbanas et al (2016), most of the landslide-prone areas in Croatia belong to hills and lowlands composed of (i) Neogene clastic rocks (marlstones), carbonate rocks and soils in the Pannonian Basin (approximately 6000 km2), and in the tectonic unit of the High Karst (approximately 160 km2), the Pre-Karst In the following text is presented a brief description of selected areas of geotectonic units particularly prone to landslides: "Gray Istria," the Rječina River Valley, the Internal Dinarides, and the Pannonian Basin.…”
Section: Geological Framework and Landslides In Croatiamentioning
confidence: 99%
“…The lack of conducted analysis is that different landslide mechanisms (slides and rock falls) were analysed simultaneously and landslide susceptibility assessment requires a multi-hazard approach, as different types of landslides may occur, each with different characteristics and causal factors, and with different spatial, temporal and size probabilities (Corominas et al, 2013). Mihalić Arbanas et al (2016) identified landslide prone areas in Croatia and BIH with hazardous processes that require a systematic approach, starting with regional landslide hazard mapping using remote sensing techniques. Based on bedrock lithology and relief types of the main geotectonic units in Croatia it was concluded that approximately 20% of Croatia or 12,000 km 2 can be described as landslide-prone areas.…”
Section: Introductionmentioning
confidence: 99%